(untitled) (AGRI-SOSIOEKONOMI, 2020)
This study aims to describe the knowledge and application of this knowledge about the typesÂ of Family Medicinal Plants (TOGA). Research location in Pinilih Village, Dimembe Sub-district,Â North Minahasa Regency. The data used in this study are primary and secondary data. The sample selection is done intentionally, namely the community members who plant medicinal plants in theirÂ homeyard. Primary data collection conducted by direct interviews with 20 community members with the help of a list of questions. Secondary data were obtained from the Pinilih Village Office, UniversityÂ Library, and the Internet. The method of analysis used in this research is descriptive analysis. TheÂ results showed that respondents had knowledge of the types of medicinal plants and knew their benefits.Â There were those who know the uses of medicinal plants without using or applying them and thereÂ were also not only knowing but also applying their knowledge. Knowledge about types of medicinalÂ plants and their benefits and how to use them is applied in family life because it is a legacy from theÂ family therefore that has been used for a long time and is still used until today. The types of medicinal plants of this family are not only planted in the yard but also in the garden.*eprm*